Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1007/bf00931726
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transport of the acidic phosphoproteins ofPlasmodium berghei andP. chabaudi from the intraerythrocytic parasite to the host membrane using a miniaturized fractionation procedure

Abstract: A miniaturized procedure for the separation of the host erythrocyte membrane from malarial parasites based on saponin lysis and density-gradient centrifugation with Percoll is described. The procedure requires only 20-35 microliters packed infected erythrocytes, is simple to perform, needs no sophisticated equipment, and can be completed in less than 2 h. Analysis of the isolated erythrocyte membranes and parasites using marker enzymes and electron microscopy revealed that both the purity and the yield of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Parasite derived antigens have been reported in P. berghei-infected eryrthrocyte membranes (Wiser et al 1988;Schetters et al 1988). Many among those were localized towards the cytoplasmic face of the membranes (Wiser et al 1988), while others were suggested to be present on the infected cell surface (Schetters et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parasite derived antigens have been reported in P. berghei-infected eryrthrocyte membranes (Wiser et al 1988;Schetters et al 1988). Many among those were localized towards the cytoplasmic face of the membranes (Wiser et al 1988), while others were suggested to be present on the infected cell surface (Schetters et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Many among those were localized towards the cytoplasmic face of the membranes (Wiser et al 1988), while others were suggested to be present on the infected cell surface (Schetters et al 1988). Our recent studies on immunoliposomes mediated delivery of chloroquine in vivo to the infected erythrocytes (Singh et al 1993;Owais et al 1995) supported the presence of neo-antigenic determinant(s) on the surface of infected erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free parasites were isolated from infected hamster RBCs as previously described (38). A lysate was made from isolated B. microti organisms by washing the pellet three times in phosphate-buffered saline, with a final resuspension in 2 ml of phosphate-buffered saline, for a starting blood volume of 4 ml (75% parasitemia).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were washed twice with HBS and erythrocytes were lysed with saponine 0.15% in HBS. Erythrocyte membranes were eliminated after centrifugation over a Percoll cushion (Wiser & Lanners 1992). Free parasites were washed three times with HBS; the weight of the pellet was evaluated and the parasites were resuspended 1:10 w/v in extraction buffer (Hepes 5 mM pH 7.5, EDTA 0.5 mM, EGTA 0.5 mM, Nonidet P40 0.05%, supplemented with the following mixture of protease inhibitors: PMSF 1 mM, Benzamidine 0.01 mM, Phenantroline 1 µg/ml, Aprotinin 10 µg/ml, Leupeptin 10 mg/ml and Pepstatin A 10 mg/ml) and frozen at -70ºC.…”
Section: Methodsmentioning
confidence: 99%